A review of the genus Trischistoma Cobb, 1913 (Nematoda: Enoplida), with descriptions of four new species from New Zealand - Zhao, Zeng Qi (Zootaxa, 2011)
Trischistoma contains four accepted species. In this paper four more new species are added to the genus. Morphologically, these four new species can be briefly characterized as follows: T. triregius sp. nov. by having a pair of lateral cervical setae; T. otaika sp. nov. by having a post-vulval uterine sac and a prominent dorsal tooth; T. waiotama sp. nov. by having a single ventromedian cervical seta; T. tukorehe sp. nov. by having two prominent dorsal teeth and long body length. Molecularly, T. triregius sp. nov., T. otaika sp. nov., T. waiotama sp. nov. and one published species, T. monohystera can be differentiated by SSU & LSU analysis. Among the four previously described species, the main distinguishing feature for T. pellucidum and T. gracile is the absence of a postvulval uterine sac, which differentiates them from T. monohystera, and T. equatoriale. All previously described species also can be differentiated by: body length and values of De Man's Indices a, b, c, c' and V. A key is provided for all eight species of the genus.